The Contribution of Master Chin Kung in World Peace and Interfaith Dialogue - Amsal Bakhtiar (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2005)
Master Chin Kung’s contribution to advocating for peace and interfaith dialogue is significant. He is not only a religious leader for the Buddhist faith but also serves as a role model for followers of other religions due to his steadfastness in promoting the universal values of religion. He believes that the goal of all religions is the same, which is to realize peace and compassion among all believers. As a result, Master Chin Kung, who has been awarded an honorary doctorate from UIN Syarif Hidayatullah, tirelessly urges world leaders to prioritize peaceful approaches over war. His extensive travels across five continents further drive him to continue advancing peace and harmony among religious communities. He firmly believes that religious education is the gateway to instilling greater love for peace and compassion in individuals. Therefore, he has established various institutions and foundations aimed at disseminating the universal values of religion. Among the foundations he has established is the Multi Culture Society in Jakarta. This foundation is highly active in organizing interfaith dialogue activities and multi-faith education.